2008
DOI: 10.3844/ajessp.2008.151.156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ionizing Radiation on Antioxidant Enzymes in Three Species of Trigonella

Abstract: The response of three species of Trigonella, namely, Trigonella stellata, Trigonella hamosa and Trigonella anguina to gamma irradiation stress was investigated with respect to antioxidant enzyme induction. When dry seeds were subjected to gamma rays (0, 40, 60, 80, 100 Krad) from a cobalt source 60Co at a dose rate of 233.5 rad/ min, a dose dependent increase in the activities of ascorbate peroxidase (APOX), superoxide dismutase (SOD) and glutathione reductase (GR) was observed in both shoots and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 32 publications
6
20
0
Order By: Relevance
“…However, it is believed that thermal treatments are the main cause of the depletion in natural antioxidants (Mokbel and Hashinaga, 2005;Mohan et al, 2008;Al-Rumaih and Al-Rumaih, 2008). In this study, increasing the boiling temperature to more than 100°C seemed to cause depletion in the antioxidant content (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…However, it is believed that thermal treatments are the main cause of the depletion in natural antioxidants (Mokbel and Hashinaga, 2005;Mohan et al, 2008;Al-Rumaih and Al-Rumaih, 2008). In this study, increasing the boiling temperature to more than 100°C seemed to cause depletion in the antioxidant content (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Free radicals readily react with almost all structural and functional organic molecules, causing metabolic disorders at the cellular level. Cell membranes may lose their stability and permeability, resulting in structural damage to the cell and physiological disorders (AL-RUMAIH; AL-RUMAIH, 2008;MOGHADDAM et al, 2011). The percentage of abnormal VX04-6828 seedlings was low at 50 and 100 Gy and gradually increased at higher doses, whereas the frequency of abnormal VX04-5692 seedlings was higher than that of VX04-6828 at low radiation doses and increased with increasing radiation dose and storage time (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…A similar phenomenon was observed during our experiment in regards to SOD and GPx activities. Other authors also showed that irradiation of plants and photosynthetic microorganisms with relatively low-doses of irradiation resulted in accelerated cell proliferation, germination rate, cell growth, stress resistance, enzyme activity and increased crop yields [4,5,[22][23][24][25]. All doses provoked the decrease of CAT activity (significant only at 100 and 120 Gy) and the maximum decrease was detected at 120 Gy (62.4%), (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Irradiation processing by γ-irradiation up to a dose of 1 kGy has been recommended for quarantine treatment of legumes including soybeans [1]. Gamma irradiation can be also used to develop economically improved sorts of different plants (varietes with high productivity potential, resistant to dieases, salt and environmental factors) [2][3][4][5]. Research on the effects of γ-irradiation on food has been done with a little information avaliable on antioxidant system in plants.…”
Section: Introductionmentioning
confidence: 99%